The effect of gallic acid on Jurkat cell line - Sourani Zahra; Pourgheysari Batoul; Rafieian-Kopaei Mahmoud; Shirzad Hedayatollah; Shirzad Moien (Shahrekord University of Medical Sciences, 2015)
Introduction: Acute lymphoblastic leukemia (ALL) is the most prevalent leukemia in children. Fruits and plants have a wide range of biological functions including anti-proliferative effect. Gallic acid (GA), is a polyhydroxyphenolic compound that is widely distributed in the natural plants. The aim of the present study was the evaluation of the effect of GA on proliferation inhibition of Jurkat cells, the lymphoblastic leukemia cell line. Methods: Jurkat cell line was cultured in blood cells culture media in a standard conditions with different concentrations of GA (0-100 μm) for 24, 48 and 72 hours. The effect of GA on cell viability was measured using MTS assay. Results: Decline of cell viability to less than 50% was observed at 60, 50 and 30 μm concentrations after 24, 48 and 72 hours incubation time, respectively. Conclusion: The results demonstrated that the polyphenolic compound, GA with antioxidant capability is effective in proliferation inhibition in Jurkat lymphoblastic leukemia cell line with a time and dose dependent manner. Therefore, GA may be a potential compound for cancer prevention and treatment.